2003
DOI: 10.1136/adc.88.5.446
|View full text |Cite
|
Sign up to set email alerts
|

HBV associated nephrotic syndrome: resolution with oral lamivudine

Abstract: A 6 year old boy presenting with a five month history of fever, lethargy, and anorexia, was found to have hepatitis B associated membranous glomerulonephropathy and nephrotic syndrome. After two months treatment with oral lamivudine, his proteinuria cleared and serum albumin and aminotransferases normalised, associated with disappearance of hepatitis B e antigen (HBeAg) and appearance of anti-HBeAg antibodies. After 12 months, without side effects, lamivudine was discontinued. He remains well 11 months off tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 51 publications
(44 reference statements)
1
11
1
Order By: Relevance
“…In contrast, in our observational cohort with relatively young patients without arterial hypertension or Diabetes mellitus the initiation of HBV-polymerase therapy seems to contribute to a milder decrease in renal function. This observation may be explained by an improvement of renal impairment by HBV-associated membranous nephropathy as reported from small patient series or individual cases [24][25][26][27]. However, in our multivariate linear mixed effects model HBV-DNA did not show a significant association with change in eGFR.…”
Section: Discussioncontrasting
confidence: 76%
“…In contrast, in our observational cohort with relatively young patients without arterial hypertension or Diabetes mellitus the initiation of HBV-polymerase therapy seems to contribute to a milder decrease in renal function. This observation may be explained by an improvement of renal impairment by HBV-associated membranous nephropathy as reported from small patient series or individual cases [24][25][26][27]. However, in our multivariate linear mixed effects model HBV-DNA did not show a significant association with change in eGFR.…”
Section: Discussioncontrasting
confidence: 76%
“…Although deposition of HBeAg in renal tissues by immunostainings could not be confirmed, excess HBeAg originated from patients with high HBV-DNA level might influence the development of HBV-associated nephropathy. As reported previously, antiviral treatments such as IFN [Garcia et al, 1985;Mizushima et al, 1987;de Man et al, 1989;Lisker-Melman et al, 1989;Wong et al, 1992;Conjeevaram et al, 1995;Lin, 1995;Bhimma et al, 2002a,b] or lamivudine [Connor et al, 2003;Filler et al, 2003;Okuse et al, 2006] were effective for the HBVassociated nephropathy in this study.…”
Section: Genetic Characteristics Of Hbv Strains In the Patients With supporting
confidence: 65%
“…Antiviral therapy has been recommended in many studies for HBV-GN since it can effectively inhibit HBV replication and attenuate proteinuria [9,[25][26][27][28][29][30][31][32][33] . Our results demonstrated that antiviral therapy could significantly improve the remission rate of proteinuria, the clearance rate of HBeAg, and renal progression.…”
Section: Discussionmentioning
confidence: 99%